Visual framing in the German movements for gay liberation and against nuclear energy. Issue 4 (8th August 2022) - Safaian, Dorna; Teune, Simon
Abstract : While the framing approach in the field of social movements has relied on analysing texts to the neglect of images, recent attention to visual framing in the field of media and communication studies largely overlooks the visual communication of social movements. This article addresses this gap by adapting methods derived from art history to unpack the nuances of meaning in movement-constructed images. It analyses the visual framing in posters of two German social movements, the movement for gay liberation and the movement against nuclear energy. Highlighting the need for information about a given movement's history to socially contextualise how its images are likely to be read in context-specific times and places, we carve out the diagnostic, prognostic and motivational dimensions of visual framing. The analysis shows how images speak to viewers, arguing for visual analysis as an advisable supplement to studying textual framing in social movements.